Assessment of CO2 and O2 spatial variability in an indigenous aquaculture system for restoration impacts - Lechner, Evan; Rii, Yoshimi M.; Ruttenberg, Kathleen; Kotubetey, Keli‘iahonui; Sabine, Christopher L. (Frontiers in Marine Science, 2022)
Patterns of spatial variability in carbon dioxide (CO2) and oxygen (O2) were assessed within an Indigenous Hawaiian fishpond undergoing active ecosystem restoration. The brackish, tidal fishpond is located within Kāneʻohe Bay, Oʻahu, Hawaiʻi. Following a year of monthly discrete sampling, a significant shift in dissolved inorganic carbon (DIC) and percent O2 saturation was observed along the north-south axis within the pond. The south end of the pond displayed higher DIC (+35 μmol·kg⁻¹) and lower percent O2 saturation (-19%) than the north end, which exhibited values similar to those observed in water entering the fishpond from the bay. Water quality parameters and inequal proximity to water flux sites suggested that a difference in residence time may exist along the north-south axis. In addition, ΔTA/ΔDIC relationships revealed a respiration signal in the south end of the pond, which was enhanced at depth. While physical processes strongly affect CO2 and O2 across various temporal scales, spatial patterns in biological processes may also affect variability within the fishpond. Here we discuss the implications of the measured water properties of the fishpond, which in turn may impact Indigenous resource management decisions to preserve its viability as a healthy habitat for the intended species.